MODEL PEMBELAJARAN THINK PAIR SHARE: UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SMP NEGERI 53 MUARO JAMBI - Tiara Dewi Cahyani; Yudi Kurniawan (STKIP Pesisir Selatan, 2026)
This research was motivated by the low interest and cognitive learning outcomes of eighth-grade students in Islamic Religious Education (PAI) at SMP Negeri 53 Muaro Jambi, which was caused by the learning process that was still conventional and teacher-centered. This study aimed to determine whether there was a significant influence of implementing the Think-Pair-Share (TPS) cooperative learning model on students' learning outcomes in the material